Partnerships and Collaborations: The Right Alliances for Clinical Trials in Africa - Olusola Solarin; Sulma I. Mohammed; Ntokozo Ndlovu; Verna Vanderpuye; Victoria Olaiya (JCO Global Oncology, 2020)
Africa attracts < 1% of all trials conducted around the world. The implication is that proof of safety and efficacy in Africans is lacking for a lot of new therapies. The sizeable proportion of approximately 20% of the global population that Africa represents largely does not have empiric data to support use of new therapies in a population with a distinct genetic and racial profile. Beyond the imperative of evidence-based interventions, Africans carry a disproportionately heavy burden of certain diseases, including prostate cancer, sickle cell anemia, and malaria. It therefore provides opportunity for efficient recruitment of participants for trials for such diseases. However, this advantage has not convinced sponsors to carry out clinical trials in Africa. India and China each have roughly the same population size as Africa, but each presents just one regulatory jurisdiction for clinical trials. Africa has 54 countries, and a sponsor would theoretically need to file 54 different applications to cover the entire continent. Collaboration and partnership among all stakeholders in the clinical trial ecosystem will reduce the burden on sponsors and make Africa competitive as a destination for clinical trials. Collaboration among national regulatory agencies will enable Africa to be treated as one regulatory jurisdiction and reduce administrative burden. Sites and researchers can partner to improve quality, attain necessary certifications, and increase overall efficiency. Central to all of these are clinical research organizations that can coordinate and work across borders to make clinical trial projects seamless. Ultimately, patients will benefit as quality of clinical practice improves and access to new therapies is enhanced.